Inhabiting the In-Between: Childhood and Cinema in Spain's Long Transition, Sarah Thomas (2019). Issue 1 (1st March 2022) - Marsh, Steven
Review of: Inhabiting the In-Between: Childhood and Cinema in Spain's Long Transition, Sarah Thomas (2019)Toronto: University of Toronto Press, 240 pp., ISBN 978-1-48750-488-5, h/bk, $77.00